The Relationship Between Neuropsychological Functioning and Mental Health Outcomes of Chronic Alcohol Users Involved in Counselling: Prediction of Treatment Outcome. (27th August 2014) - Desfosses, Melissa; Meadows, Holly; Jackson, Martin; Crowe, Simon F
<x xml:space="preserve">Abstract</x> This study examined the neuropsychological profile, mental health outcomes, and coping strategies of chronic alcohol users involved in drug and alcohol counselling and investigated whether these factors could predict treatment outcome. The findings indicated that as compared with controls, chronic alcohol users demonstrated significant deficits in visuospatial, memory and executive functioning, and a higher level of emotional distress. At a 3‐month follow‐up, memory ability was found to significantly predict the percentage of goals achieved in counselling, the likelihood of dropout from therapy, and the likelihood of remaining abstinent. The value of further research into the influence of additional factors, such as executive functioning, mood, and coping strategies, on treatment outcomes in a larger sample was also supported.